BALANCED SCORECARD SEBAGAI PENGUKURAN KINERJA MASA DEPAN SUATU ORGANISASI - Krisna, Robi (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
Performance appraisal is essential for a company. To win this increasingly fierce global competition, the performance of an organization must improve from one period to the next. Nowadays, the measurement of financial performance adequately reflects the real organizational performance, thus developing a Balanced Scorecard concept. The Balanced Scorecard concept measures the performance of an organization from a financial perspective, a customer perspective, an internal business process perspective, a growth and learning perspective. The concept of the Balanced Scorecard is in fact the translation of the strategy and objectives a company wants to achieve in the long term, which are then measured and monitored on an ongoing basis. This paper focuses on the application of the Balanced Scorecard concept in several American companies. Various problems and problems arising from the application of the Balanced Scorecard concept become input for companies or business organizations that wish to apply this concept. Also this concept will help companies to measure performance more accurately and accurately.